2012
DOI: 10.1007/s11284-012-0948-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vertical stratification of Syrphidae (Diptera) in an oak‐hornbeam forest in northern Italy

Abstract: There is growing interest in the vertical stratification of forest biodiversity, but little is known about this aspect for Syrphidae living in forests. For this study, seven Malaise traps were suspended in the canopy and seven were placed on the ground, in a lowland forest in northern Italy. Altogether, 868 specimens of Syrphidae were collected; 229 from the canopy and 639 from the ground, comprising a total of 53 species. Three species [(Ceriana conopsoides (Linnaeus), Eupeodes corollae (Fabricius), Psilota a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…As already observed in other insect groups (Birtele & Hardersen 2012;Stireman et al 2012;Hardersen et al 2014;Di Giovanni et al 2015), the canopy community of Spheciformes at "Bosco della Fontana" is markedly different from that of the understory. Previous studies performed in temperate forests also showed a vertical stratification in the community composition of hymenopterans (Vance et al 2007;Pucci 2008;Sobek et al 2009;Ulyshen et al 2010Ulyshen et al , 2011.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…As already observed in other insect groups (Birtele & Hardersen 2012;Stireman et al 2012;Hardersen et al 2014;Di Giovanni et al 2015), the canopy community of Spheciformes at "Bosco della Fontana" is markedly different from that of the understory. Previous studies performed in temperate forests also showed a vertical stratification in the community composition of hymenopterans (Vance et al 2007;Pucci 2008;Sobek et al 2009;Ulyshen et al 2010Ulyshen et al , 2011.…”
Section: Discussionsupporting
confidence: 57%
“…In both tropical and temperate forests, canopies can provide resources which are seasonally unavailable in the understory (Ulyshen et al 2010) and can offer nesting sites for specialized saproxylic organisms (Sobek et al 2009;Ulyshen et al 2011b). In certain conditions, the canopy layer may also work as aggregation point for several flying insects during mating swarming (Birtele & Hardersen 2012;Stireman et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goulson & Wright, 1998;Branquart & Hemptinne, 2000;Jauker et al, 2009;Birtele & Hardersen, 2012), one aspect that has received relatively little attention is the interspecific structure of syrphid assemblages. The structure of plant and animal communities is a product of many interacting processes.…”
Section: Introductionmentioning
confidence: 99%